Duodenal infusion of different nutrients and the site of gaseous stimulation influence intestinal gas dynamics - Harder, Hermann; Hernando-Harder, Ana C.; Franke, Andreas; Ergül, Gülşah Sultan; Krammer, H.; Singer, Manfred V. (Scandinavian journal of gastroenterology, 2006)
Objective. Excessive intestinal gas can be involved in postprandial abdominal symptom generation, but whether the small bowel influences intestinal gas dynamics, depending on the ingested meal, remains to be demonstrated. We compare the intestinal response to a proximal and distal small intestinal gas challenge during different duodenal nutrient components. Material and methods. We randomly studied 32 healthy subjects, twice, on different days with a gas mixture infused at 12 ml/min either directly into the proximal jejunum or into the ileum; during duodenal lipids, amino acids, glucose, at 1 kcal/min each, or saline (n=8 for each group). Gas evacuation was monitored continuously and abdominal perception and girth changes were assessed. Results. In response to the jejunal gas challenge, duodenal lipids delayed intestinal gas clearance more potently than amino acids (733±26 ml and 541±108 ml final gas retention; p<0.001), but when gas was directly infused into the ileum the retained volumes were much smaller (271±78 ml and 96±51 ml; p<0.001). During duodenal glucose, intestinal gas clearance following jejunal or ileal gas infusion was not significantly influenced. Abdominal perception in response to the jejunal and ileal gas challenge only increased slightly during duodenal lipids (2.0±0.3 score and 2.3±0.6 score; p<0.05 versus control). Conclusion. Postprandial intestinal gas clearance is hampered by duodenal lipids and amino acids but not by glucose. Specific inhibitory effects are more pronounced when gas is infused into the jejunum, which underlines the importance of the small intestine in postprandial gas retention.